Carbon fiber reinforced poly(ether ether ketone) rivets for fastening composite structures. (15th January 2022) - Absi, Christophe; Alsinani, Nawaf; Laberge Lebel, Louis
Abstract: Although composite materials are now commonly present in numerous aerospace applications, metallic bolt-type fasteners are still currently used despite their several drawbacks regarding weight, corrosion, and lightning strike hazards. This study explores an alternative fastening solution with the use of an innovative carbon fiber reinforced poly(ether ether ketone) (CF/PEEK) rivet. To produce such rivets, an automated riveting machine was developed. CF/PEEK blanks were cut from pultruded continuous fiber rods. The blanks were then heated beyond the matrix's melting temperature, by Joule effect. They were then molded directly into carbon fiber reinforced epoxy plates. The duration of the riveting process was 35 s from the beginning of the heating until the opening of the riveting robot to recover the joint. CF/PEEK rivets submitted to shear held up to 8.7 kN/g, while titanium fasteners held up to 4.7 kN/g. In tension, CF/PEEK rivets held up to 5.7 kN/g, while titanium fasteners held up to 3.0 kN/g. While the titanium fasteners showed a different mechanical behavior based on the hole-to-shank gap, the CF/PEEK rivets adapted to the different hole dimensions and no differentiated mechanical behavior was observed for the hole diameter investigated.